An exploratory study of the acceptability of indoor residual spraying for malaria control in upper western Ghana - Vitalis Mwinyuri Suuron; Lillian Mwanri; George Tsourtos; Ebenezer Owusu-Addo (BMC, 2020)
Abstract Background Despite the implementation of the World Health Organisation's recommended indoor residual spraying (IRS) intervention in the upper west region of Ghana to reduce malaria morbidity and mortality, the uptake of this intervention remains low. This study explores the facilitators and barriers to the acceptability and community uptake of indoor residual spraying in a highly endemic region of Ghana. Methods The health belief model (HBM) and realist evaluation framework were used to inform the study. A qualitative enquiry was conducted between April to October 2016. Data were collected through focus group discussions and semi-structured interviews with program stakeholders including community members, AngloGold Ashanti malaria control (AGA Mal) spray operators, and AGA Mal officials. Results A total of 101 people participated in the study. Considerable barriers to community acceptance of indoor residual spraying (IRS) were found, including, dislike of spray insecticides, inadequate information, religious and cultural beliefs, perceived low efficacy of IRS, difficulties with packing, unprofessional conduct of IRS spray operators, and other operational barriers to spraying. Facilitators of IRS uptake included a perceived effectiveness of IRS in preventing malaria and reducing mosquito bites, incidental benefits, respect for authority, training and capacity building, and sensitization activities. Conclusion The numerous barriers to indoor residual spraying acceptance and implications show that acceptance levels could be improved. However, measures are required to address householders' concerns and streamline operational barriers to increase community uptake of indoor residual spraying.